Perubahan Tinggi Sel Epitelium Villi Jejunum Marmut ( Cavia porcellus L.) Setelah Pemberian Teh Hijau - Muliani, Hirawati (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2015)
The research of the Guniea Pig Jejunum Villi Epithelium Cell Height After Â Given With Green Tea is aimed to know the effect of green tea on ventriculus villi epithelium cell height of female guinea pig. Twenty four female guinea pig were acclimated during 1 week and then alloted into 4 group, each group was treated as follows : P0 : treated with boiled water (= control) P1 : treated with 3 gram green tea / 200 cc water P2 : treated with 5 gram green tea / 200 cc water P3 : treated with 7 gram green tea / 200 cc water Green tea water was given by spuit without needle to the mouth of guinea pig. Amount of green tea water was 20 ml / test animal/ day. Long of the treatment was 2 months. Replication was 6 times. Main parameter observed was the change of jejunum villi epithelium cell height. Supporting parameters were guinea pig body weight after treatment, room temperature, and room humidity. Quantitative data was analyzed by varians analysis with Completely Random Design. The result of the research was given of green tea has no effect to the guinea pigÂ jejunum villi epithelium cell height , and green tea decreases guinea pig body weight after treatment. Â Keywords : Epithelium cell jejunum villi,green tea, guinea pig.